Drones, urban informality and digitalization. Understanding the capacities and opportunities using UAS for planning and monitoring upgrades on informal settlements. - Sanchez Guzman, Santiago (NWV Verl., 2018)
Der Autor demonstriert am Beispiel der Entwicklungsproblematik von informellen Siedlungen in Medellin, welche Bedeutung Drohnen zur Beschaffung von Informationsgrundlagen in Planungs- und sozialräumlichen Transforamtionsprozessen zukommen kann und welche Probleme und Chancen aus technischer wie aus planerischer Sicht damit verbunden sind.

This paper takes a planning perspective to explore the capacities and opportunities offered by UAV and UAS (Drones) on supporting planning and monitoring processes of informal settlement upgrading. It proposes that drones can be used to achieve those purposes in two ways. On the one hand, by understanding how to use drone's aerial photography in photogrammetry supporting the production of 3D Digital Elevations Models (DEMO) and Object Detection of natural and built environments. On the other hand, by exploring the opportunity in taking advantage of drone's cost-effective and practical performances assisting in the monitoring of infrastructure and neighbourhood upgrading processes, not only to institutions and experts but also to the communities themselves (supporting CBM processes). It combines theories from economists Joseph E. Stiglitz and Amartya Sen as a conceptual framework for the discussion of these drone's capacities and opportunities. Based on the theory of 'information asymmetry' proposed by Stiglitz. It will argue that drones can effectively support processes of data acquisition in informal settlements and mitigate forms of socioeconomic inequality and asymmetrical access to information. In line with Sen's remarks on how democratic access to information is key to decision-making, it proposes that by using drones. poor communities can increase their accessibility to their own settlement's aerial view, lifting their capacity to produce own information and increasing their participation in planning local territories. To make these conceptual claims tangible, the author explains how drone footage can be turned into 3D models and what they provide in terms of spatial knowledge and for analytical purposes. Finally, the paper provides technical insights into how to use the aerial photography acquired by drones to empirically produce 3D models and for analytical purposes. The latter is based on original footage conducted by the author using UAS technology in Medellin, Colombia, in November 2016 and its further transformation into 3D models for spatial and morphological neighbourhood analysis.
Keywords: Stadtplanung; Stadtentwicklung; Informationsgewinnung; Planungsgrundlage; Digitalisierung; Drohne; Siedlungsstruktur; Informelle Siedlung